2020
DOI: 10.1159/000506253
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Regional Citrate Anticoagulation for Continuous Renal Replacement Therapy: An Observational Study

Abstract: Introduction: Regional citrate anticoagulation (RCA) is the recommended anticoagulation modality for continuous renal replacement therapy (CRRT). RCA was associated with a low rate of complications in randomized controlled trials. However, little is known about the type and rate of complications in real life. We sought to describe complications associated with RCA in comparison with those associated with heparin anticoagulation. Methods: In our institution, RCA has been the default anticoagulation modality for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
16
0
4
Order By: Relevance
“…Hypocalcemia was reported 22-25.7% and 5.3% separately during CKRT and TPE respectively [14][15][16]. In our study, 147 instances of hypocalcemia < 1 mmol/L occurred over 203 treatments (72%) in 57 of 63 (90%) patients.…”
Section: Discussionmentioning
confidence: 47%
“…Hypocalcemia was reported 22-25.7% and 5.3% separately during CKRT and TPE respectively [14][15][16]. In our study, 147 instances of hypocalcemia < 1 mmol/L occurred over 203 treatments (72%) in 57 of 63 (90%) patients.…”
Section: Discussionmentioning
confidence: 47%
“…However, maintenance hemodialysis patients with full public expenditure, who can get timely and satisfactory help from family members when encountering problems, have high family income, think that their personal health is good, and have no religious beliefs, have a higher satisfaction with the quality of life [ 17 ]. Bianchi et al [ 18 ] used a special scale for chronic kidney disease to investigate the quality of life of 102 patients with MDH and compared it with those in general health. The results confirmed that the nutritional status and beliefs of dialysis patients have a greater impact on their quality of life.…”
Section: Related Workmentioning
confidence: 99%
“…Most existing RCA protocols recommend that either the adjustment of the blood flow or the replacement fluid/dialysate rate should be applied to correct acidbase disturbances during CRRT [21][22][23][24][25]. More specifically, a decrease of blood flow and/or an increase of replacement/dialysate fluid flow are considered as sufficient options to correct alkalosis, especially, if the most common modalities CVVHDF (continuous veno-venous hemodiafiltration) or CVVHD (continuous veno-venous hemodialysis) are applied.…”
Section: Discussionmentioning
confidence: 99%